Migrasi orang-orang Madura ke dusun sendang biru, 1980-1994 - Rikat L Sofyan (Historiography: Journal of Indonesian History and Education, 2023)
Madurese are one of the tribes in Indonesia that have high mobility. They migrate from their home areas to other areas in search of a more decent livelihood. Of the various Madurese migration destinations in the archipelago, Malang is one of them. Malang is an area with various aspects in it, such as education, culinary, tourism, and fisheries. This paper aims to narrate how the arrival of Madurese immigrants to South Malang, precisely to Sendang Biru in the period 1980 – 1994. The author uses the historical method by conducting in-depth readings of informal archival sources (newspapers), books, articles, and direct tracing through the process of interviews and field observations. In accordance with the Migration Theory, this paper shows that the potential for fishery resources in Sendang Biru can attract immigrants from Madura, especially fishermen and traders. From the process of in-migration of Madurese to Sendang Biru, various impacts arise, in which Sendang Biru Hamlet has a heterogeneous population that lives side by side, because of this, various social, cultural and economic impacts arise. Even though they live side by side with different cultural backgrounds, they show tolerance for one another and do not highlight their respective ethnic identities.Suku Madura merupakan salah satu suku di Indonesia yang mempunyai mobilitas cukup tinggi. Mereka bermigrasi dari daerah asal ke daerah lainnya untuk mencari penghidupan yang lebih layak. Dari berbagai daerah tujuan migrasi orang Madura yang ada di Nusantara ini, Malang merupakan salah satunya. Malang merupakan daerah dengan berbagai aspek di dalamnya, seperti pendidikan, kuliner, pariwisata, hingga perikanan. Tulisan ini bertujuan menarasikan bagaimana kedatangan para imigran Madura ke Malang Selatan, tepatnya ke Sendang Biru pada periode 1980 – 1994. Penulis menggunakan metode sejarah dengan melakukan pembacaan mendalam terhadap sumber-sumber arsip informal (surat kabar), buku, artikel, dan penelusuran langsung melalui proses wawancara dan observasi lapangan. Sesuai dengan Teori Migrasi, dalam tulisan ini menunjukkan bahwa adanya potensi sumber daya perikanan di Sendang Biru dapat menarik kedatangan para imigran dari Madura, khususnya para nelayan dan pedagang. Dari proses migrasi masuk orang Madura ke Sendang Biru menimbulkan berbagai dampak, di mana Dusun Sendang Biru memiliki penduduk heterogen yang hidup saling berdampingan, karena hal tersebutlah timbul berbagai dampak sosial, budaya, dan ekonomi. Meski saling hidup berdampingan dengan latar budaya yang berbeda, mereka saling menunjukkan sikap toleransi satu sama lain serta tidak menonjolkan identitas kesukuan masing-masing.